PÉREZ GONZÁLEZ, Fernando T. (Ed.): Joaquín Sama y la Institución Libre de Enseñanza en Extremadura. - Fernández Gañán, María Isabel (Anales del Seminario de Historia de la Filosofía, 1998)
Sin resumen